When and how is team cognitive diversity beneficial? An examination of Chaxu climate - Jiaojiao Qu; Shuming Zhao; Man Cao; Jintao Lu; Yuan Zhang; Yanhong Chen; Rongmin Zhu (Heliyon, 2024)
The workforce is becoming increasingly heterogeneous in terms of age, gender, race/ethnicity, education, values, cognition, and culture. Thus, team diversity management is regarded as an important development strategy that organizations can use to gain advantages. However, in the diversity literature, empirical studies investigating the effects of cognitive diversity on creativity have not yielded conclusive findings. This has called into question the importance of team cognitive diversity. To address this, we investigate when and how team cognitive diversity fosters individual creativity. Drawing on the categorization-elaboration model (CEM) and literature on Chaxu climate, we develop a multilevel mediated moderation model in which the team Chaxu climate is treated as the moderator and team knowledge sharing is treated as the mediator. Using two-wave paired data collected from 46 teams and 368 members, we find that Chaxu climate mitigates the positive effect of team cognitive diversity on team knowledge sharing. In turn, team knowledge sharing mediates the interaction effect between team cognitive diversity and Chaxu climate on individual creativity. Our study facilitates a shift from an automatic-oriented lens to a contingent-oriented lens by identifying a new contingent factor and advances research on the underlying mechanisms by identifying a new process factor. Ultimately, this study enriches our knowledge on the function of cognitive diversity in the field of business strategy.